Kesepian perempuan lajang pada dewasa awal - Amelia Fakhrun Nisa; Fattah Hidayat; Mohammad Bisri (Flourishing Journal, 2021)
Abstract: This research is aimed to know the lonelinessof sigle women on their early adult- period. The research is using qualitative method with fenomenology approach on three women on their early adult period who feel lonely. The data collection is using structural interview, open questionnaire, and the participants as the observers. The technique of data analysis is by using fenomenology technique. Based on the result of the analysis of this research, the conclusions acquired are as follow: (a) kind of loneliness for single women is feeling along and unreachable or unrealized dreams, (b) kinds of loneliness according to Brehm (1992), those which has existed are also appeared on every participant differently, (c) type of the loneliness in which the three participant are into is emotional loneliness, (d) the causes of loneliness are mostly due to relationships with someone, environment or a situation, and how they could build the expected relations, and (e) the reaction given were positive and negative based on the explanation of the participants which reacted in some ways such ignoring, denying, and responding. Keywords: loneliness; early-adult women; single Abstrak: Penelitian ini bertujuan mengetahui mengenai kesepian perempuan lajang pada dewasa awal. Jenis penelitian yang diambil adalah kualitatif, dengan pendekatan fenomenologi pada tiga perempuan dewasa awal lajang yang kesepian. Pengumpulan data menggunakan wawancara semi terstruktur, kuisioner terbuka, partisipan sebagai observer. Teknik analisis data dilakukan teknik data fenomenologis. Berdasarkan analisis yang dilakukan, diperoleh simpulan sebagai berikut:a)Jenis perasaan kesepian bagi perempuan lajang ialah merasakan sendiri dan harapan yang belum terpenuhi atau terwujudkan b) jenis –jenis perasaan kesepian berdasarkan Brehm, yang sudah ada juga muncul pada setiap partisipan, tetapi berbeda-beda. c) Bentuk kesepian yang mana ketiga pertisipan termasuk dalam kategori kesepian emosional. d) Penyebab kesepian lebih kepada menjalin hubungan dengan orang lain atau seseorang, lingkungan atau situasi dan bagaimana membangun hubungan yang diharapkan. e) Reaksi yang muncul berupa sikap negatif dan positif, yang mana semua menurut dari paparan partisipan. Kemudian membentuk model reaksi berupa mengalihkan, menghindar dan menanggapi reaksi tersebut. Kata kunci: kesepian; perempuan dewasa awal; lajang